International Tour de Banyuwangi Ijen impacts to local community development in Ijen Crater - Banyuwangi - Pambudi, Panji Sekar; Hariandi, Mohammad Sabiq Irwan (Journal of convention & event tourism, 2021)
The aim of this research is to analyze economic, social, and environmental impacts of International Tour de Banyuwangi Ijen (ITdBI) to local community development in Ijen Crater - tourist destination in Banyuwangi. The research subjects were local communities, public figures, tour and travel agents, hotels, restaurants, and related institutions such as government, Statistics Bureau, Culture and Tourism Department, Regional Development Board, Nature Conservation Agency of Regional Conservation Section V, and South Banyuwangi Forest Management Unit. Data were collected by using observation, live-interview, questionnaire, and archival collection method from the aforementioned relevant institutions in Banyuwangi. Pearson's Correlation Coefficient was applied to analyze economic impacts. Cross Tabulation with Chi Square used to analyze socio-cultural impacts. Qualitative data analysis used to examine environmental impacts. The results showed that ITdBI gave impacts to the local community development. Economically, it contributed 100% increasing rate for ticket revenue, 43% increasing revenue for Small and Medium Enterprises, and 37% for decreasing unemployment rate. Socially, it contributed to 11.6% increasing rate for prosperity, 11.1% for the local communities' satisfaction level, and 44.4% for the local communities' participation. Environmentally, it contributed to the continuous waste management and conservation of natural habitat of both Ijen endemic flowering plant such as Edelweiss and animals such as Lutung Jawa and deer.